The Job Satisfaction Among Government School Teachers - Ammara Nawaz Cheema , Mohammad Saleh Bataineh , Zahid Khan , Hamda Khan , Zahid Iqbal (Migration Letters, 2024)
Job satisfaction of teachers lead to quality teaching which produce talented scholars, researcher, scientist. As a result, the country grows in term of GDP and other economic terms. In the present paper, job satisfaction among the primary school teachers is investigated. The study area is Chakdara and its nearby villages, Khyber Pakhtunkhwa. The data is analysis by Minitab version 19. Total of 39% teachers were found highly satisfied, 29% teachers are moderate satisfied, 11% are low satisfied, 14% are un-satisfied, and 7% are highly un-satisfied. In order to assess the factors significantly associated with level of satisfaction of teachers, ordinal logistic regression model is used. The model produces that teacher cooperation, teacher workload, and teacher [1]perceptions of student discipline in school are the factors most closely related to teacher job satisfaction. The workload of the teachers can be deal by appointment of new teachers, teachers’ cooperation can be ensuring by developing friendly environment, and discipling among students can be ensure by awareness, and by parent’s support.